Modelling Sustainable Urban Stormwater System In Diamond City Using Swmm - Lee, Yin Tung (Universiti Sains Malaysia, 2021)
The urbanization process leads to a higher possibility of flooding. As the land use has changed from pervious to impervious surface, the natural infiltration of stormwater into the ground becomes lesser. The change of land use causes more surface runoff when there is heavy rainfall. When the drainage capacity is incapable of catering to the volume of runoff, the flood will occur eventually. In this study, the retention pond is used as a device to mitigate flooding from happening in the study area. The drainage system in the study area located in Diamond City in Mukim, Semenyih, Daerah Hulu Langat, Selangor Darul Ehsan is modeled and simulated using EPA Storm Water Management Model (SWMM). The objectives of the study are to conduct SWMM modelling on the drainage system in Diamond City, evaluate the efficiency of the drainage system for different years ARI, and evaluate the efficiency of retention ponds in the study area for different years ARI. SWMM is widely used in planning, analysis, and designing urban drainage systems. The main reason for the chosen study area is largely due that it is very susceptible to flooding. Based on the calculation, the time of concentration is 21.93minutes where the overland flow time is 5.92 minutes and the drain flow time is 16.01 minutes. Hence, a 30-minutes storm duration is used. Based on the result, the peak flow at the outfall of the drainage system is 4.46 m3/s for 100 years ARI while the peak flow for 10 years ARI is 3.85 m3/s. The higher the ARI, the drainage system is more susceptible to overflow or flooding. The result also shows the percentage of flow attenuation of the retention pond is around 90%.